Musical Analysis of Egungun Eyo and Aladoko in South Western Nigeria - Asaolu, Opeyemi Adeyinka (NIU Journal of Humanities, 2022)
The study traced the origin and development of Eyo and Aladoko Masquerades as well as their musical components. It assessed, through analysis, performance techniques of each of the masquerade’s music as resource material for African Arts Music. Finally, it also examined the socio-cultural context in which each of the masquerades existed. This was done with a view to explicating the functions of music in the performances of Eyo and Aladoko among the people of Lagos and Ado-Ekiti respectively. The study employed both primary and secondary sources of data collection. Primary source included in-depth oral interviews conducted with 14 purposively selected persons comprising the Odolofin of Ado-Ekiti, Akinshiku of Lagos and other prominent historians in Ado-Ekiti and Lagos. In addition, participant observation method was employed during the performances of Eyo masquerade in Lagos Island and Aladoko masquerade in Ado-Ekiti. During the performances, audio-visual recording was carried out camcorder, digital camera and digital sound devices. Secondary source included books, journal articles, newspapers and the Internet. The collected data were transcribed and analysed within the ethnomusicological framework. The results showed that while the origin of Egungun Eyo was traced to the colonial period in Nigeria that of Egungun Aladoko was traced to the pre-colonial era. The results also showed that while the performance of music ushered in a time of prayer in Egungun Eyo play, it was used to correct the ills of the society in the case of Egungun Aladoko. It was also revealed that while Egungun Eyo employed a group singing technique, Egungun Aladoko was exclusively a solo performance. Furthermore, it was revealed that the performance of music in the two Egungun was done in motion. The results also showed that the music in the two Egungun were performed in the ritualistic context albeit with some elements of entertainment. The study concluded that music played significant roles in the performances of Eyo and Aladoko among the people of Lagos and Ado-Ekiti respectively.